PENGARUH ALOKASI PAJAK ANTAR PERIODE, LEVERAGE DAN PROFITABILITAS TERHADAP KUALITAS LABA - Bonefentura Soa; Sri Ayem (Universitas Muhammadiyah Makassar, 2021)
This study aims to analyze the Effect of Inter-period Tax Allocation, Leverage and Profitability on Earnings Quality. The dependent variable in this study is Earnings Quality which aims to make decisions by investors or shareholders. The independent variables in this study are tax allocation between periods, leverage and profitability. This study uses secondary data on financial statements or annual reports that have been published by companies on the Indonesia Stock Exchange. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange for the period 2016-2019. By using the purposive sampling method, the total sample in this study was 60 data from 20 companies. The analytical method used is multiple linear analysis. The results of the analysis in this study show Inter-period Tax Allocation and Profitability Has No Significant Effect on Earnings Quality. While Leverage Has Significant Effect on Earning Quality